Analisis Proses Menyerang Tim Nasional Indonesia U23 Di Piala Asia U23 2024 - Ulum, Shohibul; Apriliyanto, Rizki; Sulaiman, Ahmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to find out the attacking process of the Indonesian U23 national team competing in the 2024 Asian Cup U23 with the intention of analysing the attacking process of the Indonesian U23 national team. The research method used is quantitative descriptive method with the population of the entire Indonesian U23 national team match. With the research technique observing video recording of the match. Based on the results of the study, it can be concluded that the average process of attacking the U23 Indonesian national team through combinative attacks as many as 116 times with a percentage of 38% and direct attacks as many as 110 times with a percentage of 36% and counter attacks 21 times with a percentage of 7% and fast attacks 56 times with a percentage of 19%. The success rate of attacking is seen from attacks that lead to the opponent's goal. The total shots of the Indonesian U23 national team to the opponent's goal were 79 attempts including 21 times on target and 56 times off target. These results can be used as evaluation material for the Indonesian national team to implement an objective attacking process in the next championship. In conclusion, the process of attacking the U23 Indonesian National Team is divided into 4, namely combinative attack, direct attack, counter-attack, and fast attack. Keywords: Attacking, Goal, Indonesia, Process,